A DYNAMIC RELATIONSHIP BETWEEN CONSUMER CONFIDENCE AND RESIDENTIAL PROPERTY PRICE: EMPIRICAL EVIDENCE FOR MALAYSIA - Ismail, Nur Hafizah; Nayan, Sabri (International Journal of Property Sciences (E-ISSN: 2229-8568), 2021)
In recent years, the real estate market has become a major interest for economists and researchers. In general, property prices are influenced by the supply and demand of the real estate market. In addition to the individual’s positive expectation of the real estate market would raise the demand for housing and hence, house price indexes would increase. This study provides new knowledge on how consumer confidence in the housing industry affects residential property prices in Malaysia. Previous studies on the effect of consumer perception towards residential property in Malaysia are scarce. Therefore, the objective of this study is to determine how consumer confidence affect residential property price in Malaysia. Our study differs by focusing on the effect of consumer confidence on the housing industry and macroeconomic drivers toward residential property prices in Malaysia over the period 2004:Q1 to 2018:Q4. By using the autoregressive distributed lag (ARDL) test, the empirical results have shown the presence of long-run adjustment and indicate that consumer confidence towards the housing industry and many macroeconomic variables significantly affect residential property prices. From this finding, we have suggested that government and policymakers should be able to understand consumer confidence in the housing industry to increase consumer satisfaction and to improve consumer sentiment towards the residential property market in Malaysia.